The Effect of The Generative Learning Model Based on Cognitive Conflict Assisted by Learning Videos on The Critical Thinking Skills of Grade XI Senior High School Students - Dina Olivia (Physics Learning and Education, 2026)
Students' critical thinking skills in physics at the high school level are still low, even tho teachers have used several innovative learning models such as problem-based learning and inquiry. The models used are not yet optimal for improving students' critical thinking skills. Students are not yet able to connect prior knowledge with new knowledge to build a complete new understanding. This is because the available learning media still doesn't visually present phenomena that can spark students' curiosity and encourage their critical thinking skills. The cognitive conflict-based generative model assisted by learning videos is one of the proposed alternatives to solve the above problems. This study aims to determine the effect of a cognitive conflict-based generative learning model assisted by instructional videos on students' critical thinking skills in static fluids material. The design of this quasi-experimental research is a posttest-only control group. The study population includes all eleventh-grade high school students, consisting of two classes: XI F1 and XI F2, with a total sampling technique used for data collection. The instrument used is a critical thinking ability test sheet in the form of essay questions. The data was analyzed using a two-sample t-test. The research results show that students' critical thinking skills in the experimental class are higher than in the control class. Based on the results of the two-mean equality test, the calculated "t" value is 3.59, which is greater than the table "t" value of 2.003 at a significance level of 5%. The same treatment was given to both the experimental and control classes, except that the experimental class used a cognitive conflict-based generative learning model assisted by video learning, while the control class used the models and media commonly used by teachers in schools. This means the difference is caused by the treatment given. Therefore, the use of a cognitive conflict-based generative learning model assisted by video learning significantly affects students' critical thinking skills.